Pajak Pertambahan Nilai - Putri Charunnisa Pane; Nur Atikah; Abidzar Fikri Simamora (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Value Added Tax (VAT) is one of the key sources of state revenue within Indonesia’s taxation system. VAT is imposed on the consumption of goods and services domestically and is categorized as an indirect tax, meaning it is ultimately borne by the end consumer but collected and reported by taxable entrepreneurs. This study aims to provide a comprehensive understanding of the VAT mechanism, including its collection, reporting, and the challenges encountered in its implementation in Indonesia. The research method employed is a literature review using a descriptive-qualitative approach that analyzes laws, official documents, and academic literature. The findings indicate that although VAT significantly contributes to the State Budget (APBN), its application still faces several issues such as low taxpayer compliance, administrative complexity, and inequality in tax burden distribution. Therefore, tax policy reform and administrative improvements are needed to enhance the effectiveness and efficiency of VAT collection in Indonesia.